Rheological characterization of EVA and HDPE polymer modified bitumens under large deformation at 20 º C - González, Emma (2016)
Large amplitude oscillatory shear (LAOS) coupled with Fourier transform rheology (FTR) was used for the first time to characterize the large deformation behavior of selected bituminous binders at 20 C. Two polymer modified bitumens (PMB) containing recycled EVA and HDPE and two unmodified bitumens were tested with LAOS-FTR. The LAOS-FTR response of all binders was compared at same frequency, at same Deborah number (by tuning the frequency to the relaxation time of each binder) and at same phase shift angle d (by tuning the frequency to the one corresponding to d = 50 in the SAOS response of each sample). In all the approaches, LAOS-FTR results allowed to differentiate between all the nonlinear mechanical characteristics of the tested binders. All binders show LAOS-FTR patterns reminiscent from colloidal dispersions and emulsions. EVA PMB was less prone to strain-induced microstructural changes when compared to HDPE PMB which showed larger values of nonlinear FTR parameters for the range of shear strains tested in LAOS.